Management of Anticoagulants before and after Endoscopy - Axel Hittelet; Jacques Devière (Canadian Journal of Gastroenterology)
The risk of procedure-related bleeding while taking anticoagulants needs to be weighed against the risk of thromboembolism from discontinuing these drugs. It is not necessary to adjust anticoagulation for low-risk procedures, such as upper endoscopy with biopsy, colonoscopy with biopsy or endoscopic retrograde cholangiopancreatography with stent insertion (but without sphincterotomy). Procedures that incur a high risk of bleeding include polypectomy, endoscopic sphincterotomy, laser therapy, mucosal ablation and treatment of varices. For these procedures, warfarin should be discontinued four to five days beforehand. Depending on the risk of thromboembolism, that is based on the nature of the underlying condition, the patient may require vitamin K and/or fresh frozen plasma (to ensure that coagulation parameters are within the normal range) or heparin infusions (to ensure that some degree of anticoagulation is maintained). Low molecular weight heparin is an alternative to unfractionated heparin for select cases with a high risk of thromboembolism. Warfarin therapy may generally be resumed on the night of the procedure and may be supplemented by heparin in patients with a high risk of thromboembolism. It is not necessary to discontinue acetylsalicylic acid or nonsteroidal anti-inflammatory drugs, when used in standard doses, for endoscopic procedures. There are insufficient data to make recommendations regarding newer antiplatelet drugs, such as ticlopidine or clopidogrel, but it is prudent to discontinue these medications seven to 10 days before a high-risk procedure.